The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1001/jamapediatrics.2020.5512
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Ketoacidosis at the Time of Diagnosis of Type 1 Diabetes in Children

Abstract: Type 1 diabetes (T1D) is one of the most common chronic diseases of childhood. If left untreated, diabetic ketoacidosis (DKA), a largely preventable life-threatening complication, will occur. Currently, 19% of Canadian children and 40% of US children will present with DKA at the time of diagnosis of T1D. 1,2 Because symptoms of T1D exist before the onset of DKA, 1 risk factor for DKA is a delay in the diagnosis and treatment of T1D. Other risk factors include younger age (<5 years) and lower socioeconomic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Overall, the clinical presentation of children participating in the population-based Fr1da screening was comparable to that of children diagnosed with presymptomatic type 1 diabetes by islet autoantibody screening in natural history studies [ 7 , 11 ], or clinical trials [ 38 ], and similarly with respect to stress and anxiety levels in parents in response to screening. Previous findings from the Fr1da study indicated that psychological stress scores were transiently elevated in mothers of children diagnosed with presymptomatic type 1 diabetes in the Fr1da screening and that the distress reported by the families was low or moderate in the majority of families [ 18 ], consistent with findings in children diagnosed with islet autoantibodies in natural history studies [ 39 , 40 ] and in parents of children identified with an increased genetic risk for type 1 diabetes [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 91%
“…Overall, the clinical presentation of children participating in the population-based Fr1da screening was comparable to that of children diagnosed with presymptomatic type 1 diabetes by islet autoantibody screening in natural history studies [ 7 , 11 ], or clinical trials [ 38 ], and similarly with respect to stress and anxiety levels in parents in response to screening. Previous findings from the Fr1da study indicated that psychological stress scores were transiently elevated in mothers of children diagnosed with presymptomatic type 1 diabetes in the Fr1da screening and that the distress reported by the families was low or moderate in the majority of families [ 18 ], consistent with findings in children diagnosed with islet autoantibodies in natural history studies [ 39 , 40 ] and in parents of children identified with an increased genetic risk for type 1 diabetes [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 91%